Algorithms for evaluation of the SNOW 2.0-like stream ciphers security over residue rings against correlation attacks - Alekseychuk, A.N.; Ignatenko, S.M. (Radiotekhnika, 2018)
The class of stream ciphers obtained by replacing the SNOW 2.0 cipher in the generator scheme with a bitwise addition by an arithmetic addition modulo a power of 2 is investigated. Algorithms for evaluation of such ciphers security against correlation attacks, analogous to the known attacks on SNOW 2.0, are developed. It is shown that under certain conditions the above replacement results in a significant increasing the security of the cipher against known correlation attacks.